Between Between the real and the imaginary: the construction of the symbolic in the attack on New York. : The attack on the Twin Towers on September 11th and universal daze. - Álvarez, José Maurício (Advances in Social Sciences Research Journal, 2021)
This article examines the political participation of mythology and the imaginary and the role of the history of unexpected events. It demonstrates how the attack on the Twin Towers in New York on September 11, 2001, determined contextualization of the event and ’resymbolization.’ Working with the concept of the state of cinema, this article explores the possibilities of constructing modern culture which, based on the action of images and the movies. We analyze the North American imperial discourse, and the fabrication of a picture of the world based on a cinematographic, symbolic, and media process was - in the duel against the bad guy, and the American hero.